A reflective analysis of the Losarang-Indonesian Dayak community’s thinking culture in selecting a life partner - Mellawaty, Mellawaty; Sukestiyarno, Yohanes Leonardus; Isnarto, Isnarto; Zaenuri, Zaenuri (Institute of Advanced Engineering and Science, 2025)
This research uses a realistic ethnographic design to examine the culture of mathematical thinking in determining the match between partners for marriage in the Losarang-Indonesian Dayak community. Data were collected through field notes, in-depth interviews, and observation. Ethnomathematics as a research genre reveals important universal elements of mathematical activity, while ethnomodelling reflects ideas and the practice of community mathematics through ethical, emic, and dialectical approaches. The findings of this research indicate that ethnomathematically, the Losarang-Indonesian Dayak community have used formal language on mathematical principles to develop a knowledge system capable of sorting, pairing, calculating, and comparing the suitability of partners based on birth. Ethnomodelling is a relevant mathematical idea and concept related to arithmetic operations, sets, relations, functions, and number comparisons. Furthermore, the implication of this research is to produce didactic situations to teach the concepts of arithmetic operations, sets, relations as well as functions, and number comparisons. The didactic situation of the customary patterns of the Losarang-Dayak community can also be presented in mathematics teaching materials based on local culture. Therefore, the successful conduction of this research can enrich the repertoire of developing school mathematics learning that focuses on local culture.